COURT VERDICT ANOMALY THAT DROPPED PUNISHMENT AGAINST CHILDREN UNDER 12 (TWELVE) YEARS OLD - Sabungan Sibarani (Faculty of Law, Universitas Jenderal Soedirman, 2015)
The protection of children is a very serious problem and need to be considered better. That is because the child has a very important role in life of the nation in the future. Author emphasizes research how the legal effect of a District Court decision which is contrary to the Constitutional Court No. 1/PUU-VIII/2010. The author examines the problem with normative legal research methods. The research data shows that the victims are Doni Yoga (DY) who was aged 11 years old. Doni Yoga charged with the crime of theft under Article 363 paragraph (1) of the Criminal Code of the theft. The author concluded that the decisions of the cases by Pematangsiantar District Court has been at odds with the law and the Constitutional Court Decision No. 1 / PUU / 8/2010. However, the decision is still to be considered true and valid throughout not be appealed or an appeal that was canceled by court decision on a higher level.Keywords: Child Protection, Punishment.